2004
DOI: 10.1007/s00535-004-1448-0
|View full text |Cite
|
Sign up to set email alerts
|

Interferon therapy for aged patients with chronic hepatitis C: improved survival in patients exhibiting a biochemical response

Abstract: These results suggest that IFN treatment could reduce liver-related mortality in chronic hepatitis C patients over age 60, notably in patients showing a biochemical response and in those showing a sustained virological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 34 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…level might benefi t from IFN therapy, although they should decide the indications for IFN very carefully in this age group. Imai et al [8] reported that some aged patients with chronic hepatitis C might be recommended IFN therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…level might benefi t from IFN therapy, although they should decide the indications for IFN very carefully in this age group. Imai et al [8] reported that some aged patients with chronic hepatitis C might be recommended IFN therapy.…”
Section: Discussionmentioning
confidence: 99%
“…When such aged chronic hepatitis C patients with abnormal ALT levels consult a doctor, the fi rst problem is whether or not therapy should be used for chronic hepatitis C. Moreover, when treatment for chronic hepatitis C is decided in such aged patients, whether IFN therapy should be used or not is the second problem. However, a few studies have targeted IFN therapy and prolonged prognosis in elderly patients with chronic hepatitis C [7,8] . Until now, IFN treatment for chronic hepatitis C has mainly been introduced when patients are less than 60-65 years of age because of IFN-related side effects and safety standards in Japan.…”
mentioning
confidence: 99%
“…Although IFN therapy for chronic hepatitis C, both with standard and pegylated drugs, is commonly thought to prevent or delay HCC 5, [7][8][9]13 , in the present case severity of disease unexpectedly increased during treatment and concomitantly with viral clearance. On the grounds of its local diffuseness, the tumor was seemingly pre-existing, however neither laboratory tests nor ultrasound investigation had diagnosed it previously, and despite unhomogeneous liver echotexture with hypo-and hyperechoic scattered areas, nevertheless focal lesions were not identifiable.…”
Section: Discussionmentioning
confidence: 65%
“…Specifically, HCV-related liver cirrhosis accounts for about 4% risk per year of developing HCC [5][6] , and the tumor incidence in North America, Europe and Japan is increasing, mainly as a consequence of HCV diffusion during the previous decades 1 . Although the mechanisms by which the virus promotes hepatocarcinogenesis are not completely clear yet, interferon (IFN) therapy seems of benefit in preventing HCC, owing to antimitogenic and antioxidative properties, both in sustained virological responders and in transient biochemical responders [7][8][9] . Since tumor diffusion significantly limits an effective removal of lesions 4 , procedures for disclosing primary nodules in cirrhotics have been carefully standardized by major scientific societies 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Imai et al 16 reported that IFN therapy reduced liver-related mortality in aged patients with chronic hepatitis C, especially in those exhibiting a biochemical response as well as a sustained virological response. If this result is correct, some aged patients with chronic hepatitis C might be recommended for IFN therapy.…”
mentioning
confidence: 98%